Signaling pathways in pheochromocytomas and paragangliomas: prospects for future therapies. - Nölting, S; Grossman, AB (2012)
There is currently no completely effective therapy available for metastatic pheochromocytomas or paragangliomas. Increasing understanding of the germline and somatic mutations leading to pheochromocytoma and paraganglioma development has revealed crucial insights into the molecular pathology of these tumors. A detailed understanding of the molecular pathway alterations giving rise to pheochromocytomas and paragangliomas should allow for the exploration and development of new effective molecular-targeted therapy options for this rare but frequently fatal malignancy. Molecular analysis has shown that pheochromocytoma/paraganglioma-promoting gene mutations can be divided into two major groups-clusters 1 and 2-following two different routes to tumorigenesis. Cluster 1 mutations are associated with pseudohypoxia and aberrant VEGF signaling while cluster 2 mutations are associated with abnormal activation of kinase signaling pathways such as PI3 kinase/AKT, RAS/RAF/ERK, and mTORC1/p70S6K suggesting relevant targets for novel molecular-targeted therapy approaches which will be discussed in detail in this chapter.